Cryptocurrencies: investigation of explosivity, co-explosivity and connectedness to financial markets - Mohamed, Mariam Faiha (2022)
Cryptocurrencies have attained massive global attention shortly after its creation, thus capturing the interest of literature, with many works directed to address the price dynamics of Bitcoin and other cryptocurrencies. Price bubbles, or explosive behaviour has been documented by prior research, with its frequency increasing in recent times. Adding to this growing body of literature, this thesis is aimed at identifying explosive periods in Bitcoin and a range of altcoins with top market capitalisations through the PSY methodology. Further, co-explosivity existing between cryptocurrencies, and their interconnectedness to financial assets and indices such as S&P500, Gold, MSCI World, and so on are investigated through the aid of a logistic regression, and spillover tables. The results identified explosive periods in cryptocurrencies to align with major regulatory and economic changes to the industry. Subsequently, with shared characteristics among most cryptocurrencies, a high tendency for co-explosivity was also detected. Moreover, the results also identified cryptocurrencies to be highly isolated from financial assets in terms of both return and volatility, thus proving to be an effective hedging instrument to mitigate and diversify risk for investors. The results have noteworthy implications for investors, regulatory bodies, fund managers, and the general public. The overall dynamics of cryptocurrencies have changes recently, with its usage as a speculative instrument declining, while its increasingly being used as a store of value. Therefore, with increasing prominence among the general public, more regulation is deemed vital for this new asset class.